Effects of a Swedish master's programme on quality improvement and leadership - A qualitative study on micro, meso and macro levels of the welfare sector - Annika Nordin; Kristina Areskoug-Josefsson (Cogent Business & Management, 2020)
Improvement knowledge is recognised as an important competence for healthcare professionals in many countries. Researchers have studied the effects of improvement knowledge education but there is a lack of knowledge educations' operational effects. Research also lacks a system perspective. To address these gaps we use a model making it possible to study the welfare sector as a complex system. In this way, we intend to provide a deeper understanding of operational effects of a improvement knowledge curricula. We examine the effects of a master's programme on quality improvement and leadership in the Swedish welfare sector on micro, meso and macro levels. Twelve telephone interviews were performed with alumni exploring the experienced effects of the programme. On micro level, respondents reported that the engagement for improvement work increased and that patient/client/customer focus increased. Several personal effects were also described. On meso level, respondents described how the role as quality improvement facilitator developed and how measures were central for monitoring improvement. Several respondents believed the education contributed to improved health and welfare on macro level. To capture all effects of an improvement knowledge curricula in higher education qualitative effects on several levels of the welfare system are important to acknowledge.
Keywords: 650; clinical microsystem theory; educational effects; improvement knowledge curricula